2004
DOI: 10.1002/ca.10236
|View full text |Cite
|
Sign up to set email alerts
|

Anatomy of renal arterial supply

Abstract: A thorough knowledge of the variations of the renal artery has grown in importance with the increasing numbers of renal transplants, vascular reconstructions, and various surgical and radiologic techniques. The literature indicates that multiple renal arteries are found in 9- 76% of cadavers. The purpose of this study is to establish the incidence and characteristics of variations of renal arteries in Thais. A total of 267 Thai cadavers were dissected in the anatomy laboratory. The anatomical findings included… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

15
88
1
11

Year Published

2004
2004
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 134 publications
(123 citation statements)
references
References 11 publications
(10 reference statements)
15
88
1
11
Order By: Relevance
“…Accessory arteries were also seen both at the poles and at the hilum. 10,25 The findings of the present studies were consistent with the previous studies. Accessory arteries were not seen at the hilum.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Accessory arteries were also seen both at the poles and at the hilum. 10,25 The findings of the present studies were consistent with the previous studies. Accessory arteries were not seen at the hilum.…”
Section: Discussionsupporting
confidence: 93%
“…Some authors have reported a higher frequency on the left, 9,13,22,23 where as others have found it to be more frequent on the right side. 7,10,14 In the present study, accessory renal arteries were observed more on the left (63.63% )than on the right side (36.36%).…”
Section: Discussionsupporting
confidence: 43%
See 1 more Smart Citation
“…Usually, these vessels originate from the aorta or common iliac arteries between the levels of T11 and L4. Rarely, they may originate from the suprarenal artery, the celiac trunk, superior mesenteric, inferior mesenteric, median sacral and phrenic arteries [9][10][11] . In General, the arteries which irrigate the renal poles are thinner then the hilar renal arteries from the main renal arteries 12,13 .…”
Section: Introduction Introduction Introduction Introduction Introducmentioning
confidence: 99%
“…En la mayoría de los individuos se encuentra una arteria renal a cada lado, la que se divide previamente a su ingreso en el hilio renal, en dos o más ramas, (Testut & Latarjet, 1969;Dangelo & Fattini, 1988;Williams et al, 1995;Moore & Dalley, 2002;Khamanarong et al, 2004). Este padrón no está exento de variaciones, ya que se han descrito arterias renales dobles, uni o bilaterales (Tanyeli et al, 2006) o en menor porcentaje, tres arterias renales (Khamanarong et al;Raheem et al, 2007). Considerando la importancia de comunicar estas variaciones anatómicas, se presenta una inusual disposición de tres arterias renales.…”
Section: Introductionunclassified